Me ajudem
resolva as equações exponenciais
1) (3^2x-7)³÷9^x+1=(3^3x-1)⁴
2)2^3x+2÷8^2x-7=4^x-1
Soluções para a tarefa
Respondido por
3
Boa noite Pedrojoao
1)
3^(2x - 7)^3/9^(x + 1) = 3^(3x - 1)^4
3^(6x - 21)/3^(2x + 2) = 3^(12x - 4)
6x - 21 - 2x - 2 = 12x - 4
4x - 23 = 12x - 4
12x - 4x = -23 + 4
8x = -19
x = -19/8
2)
2^(3x + 2)/(8^(2x - 7) = 4^(x - 1)
2^(3x + 2)/(2^(6x - 21) = 2^(2x - 2)
3x + 2 - 6x + 21 = 2x - 2
5x = 25
x = 5
1)
3^(2x - 7)^3/9^(x + 1) = 3^(3x - 1)^4
3^(6x - 21)/3^(2x + 2) = 3^(12x - 4)
6x - 21 - 2x - 2 = 12x - 4
4x - 23 = 12x - 4
12x - 4x = -23 + 4
8x = -19
x = -19/8
2)
2^(3x + 2)/(8^(2x - 7) = 4^(x - 1)
2^(3x + 2)/(2^(6x - 21) = 2^(2x - 2)
3x + 2 - 6x + 21 = 2x - 2
5x = 25
x = 5
Respondido por
2
====================================
Perguntas interessantes
História,
11 meses atrás
Matemática,
11 meses atrás
Biologia,
11 meses atrás
Ed. Física,
1 ano atrás
Psicologia,
1 ano atrás